2010
DOI: 10.1509/jmkr.47.6.1070
|View full text |Cite
|
Sign up to set email alerts
|

Can Uncertainty Improve Promotions?

Abstract: Many consumer promotions involve uncertainty (e.g., purchase incentives offering the chance to receive one of several rewards). Despite retailers' heavy reliance on such promotions, much academic research on uncertainty has demonstrated examples of consumers avoiding and/or disliking uncertainty, implying that promotions involving uncertainty may not be as effective for retailers as promotions offering certain rewards. In an effort to reconcile the prevalence of uncertain promotions with the existing research,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
136
4
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(150 citation statements)
references
References 37 publications
6
136
4
4
Order By: Relevance
“…Specifically, most recently, Goldsmith and Amir (2010) Goldsmith and Amir (2010) observed a higher purchase rate for the promoted candy bar when the gift was more valued than when it was less valued. More importantly, the purchase rate of the candy bar, when coupled with a promotion that was ambiguously defined as either of the two (less or more valued) gifts, did not differ from when coupled with a more valued gift promotion (the three types of promotions were run separately, one condition at a time).…”
Section: Previous Consumer Behavior Research On Probabilistic Promotionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, most recently, Goldsmith and Amir (2010) Goldsmith and Amir (2010) observed a higher purchase rate for the promoted candy bar when the gift was more valued than when it was less valued. More importantly, the purchase rate of the candy bar, when coupled with a promotion that was ambiguously defined as either of the two (less or more valued) gifts, did not differ from when coupled with a more valued gift promotion (the three types of promotions were run separately, one condition at a time).…”
Section: Previous Consumer Behavior Research On Probabilistic Promotionsmentioning
confidence: 99%
“…The authors suggested that their findings were due to wishful thinking, which made customers focus on the best option of the ambiguously defined promotion. Extrapolating Goldsmith and Amir's (2010) findings from the product promotions domain to our price promotions domain and from unknown to known probabilities, a probabilistic price promotion that offered, e.g., a 10% chance to get a purchase for free and a 90% chance to pay the regular price would cause consumers to focus on the best possible outcome ("free"). As a consequence, such a probabilistic price promotion would be as effective and thus cheaper for a retailer than simply offering a product for free with certainty.…”
Section: Previous Consumer Behavior Research On Probabilistic Promotionsmentioning
confidence: 99%
“…This reduction leads to lower repurchasing levels after the promotion, when the product is back at its regular price level. Investigations of uncertain promotions have focused on the immediate benefits and have shown that GPDs might induce purchase incentives similar to comparable RPDs (e.g., Goldsmith and Amir 2010). However, no study has explored the consequences of GPDs for customers' IRPs and repurchasing subsequent to the promotion.…”
mentioning
confidence: 99%
“…With only the data from study 3, one might wonder if consumers are less willing to be interrupted if they are more uncertain of winning two of three games in the allotted time (cf. Goldsmith and Amir 2010). Study 2 rules that out.…”
Section: Discussionmentioning
confidence: 99%